Two new species of Curuapira Martins & Galileo, 1998 (Coleoptera, Cerambycidae, Lamiinae, Desmiphorini) - Santos-Silva, Antonio C.; Bezark, Larry G.; Galileo, Maria Helena M. (Zootaxa, 2016)
Two new species of Curuapira Martins & Galileo, 1998 are described: C. hovorei sp. nov. from Ecuador and C. armandi sp. nov. from Panama. A key to species of the genus is provided.